Person based predictive policing: lessons from selected ECtHR case law on the right to respect for private life - Warso, Zuzanna (Technology and Regulation, 2022)
This article addresses human rights requirements for person-based predictive policing. It looks into human rights standards, as elaborated in the selected European Court of Human Rights case-law on the right to respect for private life. Two groups of cases are analysed. The first group concerns the creation of police databases, watchlists and registries. The second relates to the police’s use of new technologies. The article analyses the application of the three-step test in these judgments, namely whether interference with the right was ‘prescribed by law’, whether it ‘pursued a legitimate aim’ and whether the interference was ‘necessary in a democratic society’. The article concludes that for interference with the right to privacy by a person-based predictive policing system to be justified, evidence on the effectiveness and accuracy of the system is required.